2019
DOI: 10.1111/jne.12717
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium l‐glutamate‐obesity onset is associated with disruption of central control of the hypothalamic‐pituitary‐adrenal axis and autonomic nervous system

Abstract: The hypothalamic-pituitary-adrenal axis (HPA) exerts important catabolic peripheral effects and influences autonomic nervous system (ANS)-mediated processes.Impaired negative-feedback control or reduced HPA axis sensitivity and altered ANS activity appear to be associated with the development and maintenance of obesity.In the present study, we examined the hypothesis that the central HPA axis is dysregulated favouring ANS disbalance in monosodium l-glutamate (MSG)-induced rat obesity. Glucose homeostasis, cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…Dornfest et al (1992) showed that PHZinduced anaemia could be reversed by corticoids treatment. Indeed, MSG-obese rodents exhibit hypercorticosteronaemia (Torrezan et al, 2019), a condition that is not able to prevent anaemia, as demonstrated in the present study. WAT mass accumulation, particularly in male mice (Alnaeeli et al, 2014;Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 50%
“…Dornfest et al (1992) showed that PHZinduced anaemia could be reversed by corticoids treatment. Indeed, MSG-obese rodents exhibit hypercorticosteronaemia (Torrezan et al, 2019), a condition that is not able to prevent anaemia, as demonstrated in the present study. WAT mass accumulation, particularly in male mice (Alnaeeli et al, 2014;Zhao et al, 2015).…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, excessive expansion of WAT in M-Obese rats was characterized by adipocyte hypertrophy in both visceral and subcutaneous WAT depots. Autonomic unbalance, with higher vagal hyperactivity and lower sympathetic tonus, is an evident phenomena in M-Obese rodents, which contributes to elevated WAT mass (Torrezan et al, 2019). In addition, in this obese rodent model, several hormonal and metabolic abnormalities contribute to elevated WAT mass and adipocyte hypertrophy, such as greater insulin lipogenic action (Kulyte et al, 2017), reduced lipolytic responses, higher cortisol and reduced growth hormone (GH) levels.…”
Section: Discussionmentioning
confidence: 99%
“…One group (n = 44) received a daily subcutaneous injection of monosodium glutamate (MSG) in a dose of 4 g/Kg of body weight (bw) during five consecutive days according to a previously established protocol (Olney, 1969). Elevated MSG doses to neonates provoke hypothalamic lesions, inducing lifelong obesity (Timper and Brüning, 2017;Torrezan et al, 2019). This group was denominated M-Obese.…”
Section: Hypothalamic Obesitymentioning
confidence: 99%
“…Пошкодження гіпоталамусу та порушення роботи органівмішеней негативно впливає на нейроендокринну регуляцію [19]. Досліджено можливий вплив глутамату натрію на розвиток ожиріння та появу нездорової харчової поведінки [20,21]. Враховуючи, що саме структури сірого горба гіпоталамуса беруть участь в енергетичному обміні [22], було доцільним вивчити макрота мікроструктуру даної ділянки під впливом глутамату натрію та за умов його відміни.…”
Section: «Art Of Medicine»unclassified